Territorial Planning, its Actors and Instruments. The Portuguese & Hungarian Planning System - CARDOSO, Ana Margarida Martins (Discussion Papers, 2012)
The objective of the report is to provide a comparative work on the Portuguese and Hungarian territorial planning system. It is divided into three parts: first, the explanation and comprehension of the Portuguese territorial management system, its instruments and institutions are presented, which is followed by the discussion of the same issues for the Hungarian territory - we identify instruments and institutions responsible for territorial organisation in connection with planning; and finally, a comparison of the two systems is given.